Minimum Free Energy-Based Amino Acid Sequence Permutation From Amino Acid - Lloyd-Yemoh, E; Shi, HB (International Journal of Computer Sciences and Engineering, 2025)
Computationally speaking, there are a few ways to tackle problems of rule-based permutations and iterations. This paper seeks to explore two algorithms and their possible application in the field of bioinformatics and biochemical engineering. We believe that accurately predicting RNA secondary structure formations can only be achieved by extensive analysis of specific RNA folds that have already been documented to occur in nature and others like them that have the same Amino acid sequence structure and similar minimal free energies. This paper focuses on algorithms to extract every single RNA sequence that fits a given amino acid sequence. We concern ourselves mainly with the computation intensive issue of the outputting various permutations of given protein sequences and their respective minimal free energies. Results: We present a way to computationally improve analysis of secondary structure minimization. Using C++, Sequence permutations of amino acids are extracted to be analyzed in terms of minimum free energies. ViennaRNA-2.1.6 is used to facilitate our computation of the RNA fold and the corresponding minimal free energy. The Odometer Weighted Counter (OWC) approach comes in second with its critical length of six amino acids and a computations time of 68 seconds. The Vector Permutation Mapping (VPM) approach comes in as the more desirable approach with a critical length of 10, and a computation time of 26896 seconds. All tests were made on critical path length of sequences. An output of importance to our paper is the minimal free energy of each RNA sequence that the ViennaRNA RNAfold function processes. Analysis of the resulting minimal free energies in comparison to already documented RNA strings in nature is the key to more effective secondary structure prediction.